2017
DOI: 10.1038/s41598-017-09128-x
|View full text |Cite|
|
Sign up to set email alerts
|

Microplastics in Spanish Table Salt

Abstract: Marine debris is widely recognized as a global environmental problem. One of its main components, microplastics, has been found in several sea salt samples from different countries, indicating that sea products are irremediably contaminated by microplastics. Previous studies show very confusing results, reporting amounts of microparticles (MPs) in salt ranging from zero to 680 MPs/kg, with no mention of the possible causes of such differences. Several errors in the experimental procedures used were found and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
184
5
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(215 citation statements)
references
References 38 publications
9
184
5
8
Order By: Relevance
“…Microplastic values recorded in this study are significantly lower than literature [37] and similar to 28-462 items/kg values recorded by Kim et al [38], and 50-280 items/kg by Iñiguez et al [35]. Our results are lower than 550-681 items/kg values recorded by Yang et al [34] in Chinese sea salts.…”
Section: Consideration On Analytical Techniquessupporting
confidence: 79%
See 3 more Smart Citations
“…Microplastic values recorded in this study are significantly lower than literature [37] and similar to 28-462 items/kg values recorded by Kim et al [38], and 50-280 items/kg by Iñiguez et al [35]. Our results are lower than 550-681 items/kg values recorded by Yang et al [34] in Chinese sea salts.…”
Section: Consideration On Analytical Techniquessupporting
confidence: 79%
“…On a local scale, these activities could affect at different intensities both levels and chemical composition of microplastics in table salt of marine origin. Also, long exposure time to atmospheric deposition occurring during the evaporation process of water in salt marshes could determine significant differences concerning microplastic pollution due to local inputs from winds [35]. Concerning chemical composition of microplastics, Yang et al [34] reported that PET (polyethylene-terephthalate) is the principal component of plastic found in tested table salt and this fact is associated to the higher density of PET (1.30 g/cm 3 ) in comparison to PE (0.94 g/cm 3 ) and PP (0.90 g/cm 3 ) that allow PET deposition during the salt crystal formation.…”
Section: Microplastics In Table Saltmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been found in fish and bivalve organisms, and have been shown to have negative effects on zooplankton and oysters [11][12][13][14][15][16]. Table salt from around the world has been found to contain microplastics [17,18], and the sea salt contamination, by plastic itself, has been shown to be an indicator of plastic pollution. Drinking water can also contain microplastics [19], and the potential impact on humans has been discussed [20,21], with specific negative impacts on epithelial inflammation [22] and muscle cell behaviour [23].…”
Section: Introductionmentioning
confidence: 99%